2021
DOI: 10.1007/s00109-021-02134-7
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1 mediated activation of antimicrobial peptide LL-37 in type 2 diabetic patients

Abstract: Infections are common in patients with diabetes, but increasing antibiotic resistance hampers successful bacterial clearance and calls for alternative treatment strategies. Hypoxia-inducible factor 1 (HIF-1) is known to influence the innate immune defense and could therefore serve as a possible target. However, the impact of high glucose on HIF-1 has received little attention and merits closer investigation. Here, we show that higher levels of proinflammatory cytokines and CAMP, encoding for the antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…7 ). Our results suggest that psoriasin in addition to other factors demonstrated by us 67 as well as others 17 , 34 aim to outcompete the negative consequences of high glucose. We hypothesize that these factors although partly acting independently may still be interrelated thereby strengthening the effect.…”
Section: Discussionsupporting
confidence: 60%
“…7 ). Our results suggest that psoriasin in addition to other factors demonstrated by us 67 as well as others 17 , 34 aim to outcompete the negative consequences of high glucose. We hypothesize that these factors although partly acting independently may still be interrelated thereby strengthening the effect.…”
Section: Discussionsupporting
confidence: 60%
“…Mohanty et al demonstrated that activation of hypoxia-inducible factor 1 (HIF-1) enhanced Cramp gene expression [ 28 ]. Furthermore, higher levels of proinflammatory cytokines and CAMP correlate with HIF-1 in type 2 diabetic patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mohanty et al demonstrated that activation of hypoxia-inducible factor 1 (HIF-1) enhanced Cramp gene expression [ 28 ]. Furthermore, higher levels of proinflammatory cytokines and CAMP correlate with HIF-1 in type 2 diabetic patients [ 28 ]. Since myocardial infarction results in hypoxemia [ 3 ], hypoxic effects might also play a role in modulating circulating CAMP/CRAMP levels in our experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that antimicrobial peptide LL-37 not only has anti-inflammatory effects, but also increases the expression of pro-inflammatory factors under certain conditions. For example, the expression of IL-8 in macrophages and IL-6 in dendritic cells may be enhanced by the peptide LL-37(Mohanty et al, 2021). Peptides such as defensins, LFP-20 inhibits the NF-κB signalling pathway and reduces inflammation (Rodriguez-Carlos et al, 2021;Zong et al, 2015).…”
mentioning
confidence: 99%